Development of Mathematics Didactic Design with Integration of Peer Instruction Regarding Representational Ability of High School Students - Komala, Elsa; Suryadi, Didi; Dasari, Dadan (Universitas Muhammadiyah Mataram, 2021)
This study focuses on the ability of representation with the integration of peer instruction which was developed through didactic design development research. The purpose of this research is to develop a didactic design in the form of learning tools, which are referred to in this study, namely: Lesson Plans, Teaching materials in the form of Student Worksheet in the form of student guides containing material information, sample questions, and practice questions. According to the problems experienced by students related to the ability of representation. The process of developing learning tools using Didactical Design Research (DDR), consists of didactic situation analysis, metapedadidactic analysis, and retrospective analysis. The didactic design developed was validated by 3 experts, namely 1 mathematics education lecturer and 2 high school mathematics teachers. The results showed that the learning plans were obtained in the form of a didactic design in the form of lesson plans that integrated peer instruction and worksheets for 8 meetings with the overall results of each aspect of the learning device being analyzed descriptively by revising the didactic design based on input and notes from the validator. Mathematics didactic design in high school to minimize learning obstacles related to students' representational abilities, includes 1) The material begins with the introduction of problems that are suitable for the situation and even related to the context of daily life, providing an overview of the benefits of the material to be studied, 2) Strengthening the material prerequisites presented at the first meeting, 3) Integrating peer instruction in the implementation of mathematics learning, 4) Providing scaffolding at the time of learning, 5) Student work and assignments are corrected and confirmed directly. In addition, the process of strengthening the visual representation process, modeling or mathematical expression, and the process of making written words presented on the worksheets is also carried out. Thus, the mathematical didactic design with the integration of peer instruction has provided appropriate learning activities; the purpose, depth and accuracy of the concepts and materials presented are traceable, communicative, the clarity of the images and spelling is appropriate, there is no correction given by the validator, so it can be implemented with the aim of developing students' mathematical representation abilities.